2019
DOI: 10.1016/j.ijppaw.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Age affects antibody levels and anthelmintic treatment efficacy in a wild rodent

Abstract: The role of the host immune system in determining parasite burdens and mediating within-host parasite interactions has traditionally been studied in highly controlled laboratory conditions. This does, however, not reflect the diversity of individuals living in nature, which is often characterised by significant variation in host demography, such as host age, sex, and infection history. Whilst studies using wild hosts and parasites are beginning to give insights into the complex relationships between immunity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 48 publications
3
26
2
Order By: Relevance
“…2B), with OPGs being four-fold higher than control mice, which is consistent with our previous results (Knowles et al. 2013; Clerc et al. 2019a, 2019b).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2B), with OPGs being four-fold higher than control mice, which is consistent with our previous results (Knowles et al. 2013; Clerc et al. 2019a, 2019b).…”
Section: Resultssupporting
confidence: 92%
“…5); lower production of local TNF-α was found in older, treated mice, while there was no effect of age on local TNF-α production in control mice. These interactions between host characteristics and anthelmintic treatment suggest that hosts are impacted differently by the reduction in H. polygyrus burden depending on their age or sex (see Clerc et al. 2019a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ivermectin and Pyrantel pamoate are broad-spectrum anthelminthics which target adult and larval stages (Ivermerctin) and adult stages (Pyrantel) of H. polygyrus in both laboratory and wild mice [7][8][9]. Previous work in wild A. sylvaticus found that the combination of Ivermectin and Pyrantel at 9.4mg/kg and 100 mg/kg, respectively, efficiently cleared H. polygyrus infection for ~14 days [10].…”
Section: Parasite Materials and Anthelmintic Treatmentmentioning
confidence: 99%